2021
DOI: 10.1371/journal.pone.0260570
|View full text |Cite
|
Sign up to set email alerts
|

Association between leisure-time physical activity and the built environment in China: Empirical evidence from an accelerometer and GPS-based fitness app

Abstract: To reexamine the relationship between leisure-time physical activity (LTPA) and the built environment (BE), this paper takes advantage of the massive amount of data collected by an accelerometer and GPS-based fitness mobile app. Massive LTPA data from more than 3 million users were recorded by Codoon in 500m by 500m grid cells and aggregated to 742 natural cities in mainland China. Six BE indicators were quantified using GIS at the city scale. Robust regression analysis was used to estimate the correlation bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
0
13
1
Order By: Relevance
“…The level of physical activity was assessed using the International Physical Activity Questionnaire, which has already been validated in Iran ( 17 ). The IPAQ collects PA data by asking participants to recall their vigorous and moderate activities during the last 7 days ( 18 ). Using this questionnaire, the activity level of people at home, during exercise, during travel, and in sitting activities was determined.…”
Section: Methodsmentioning
confidence: 99%
“…The level of physical activity was assessed using the International Physical Activity Questionnaire, which has already been validated in Iran ( 17 ). The IPAQ collects PA data by asking participants to recall their vigorous and moderate activities during the last 7 days ( 18 ). Using this questionnaire, the activity level of people at home, during exercise, during travel, and in sitting activities was determined.…”
Section: Methodsmentioning
confidence: 99%
“…It was found that some of the regional indicators met the normal distribution and could be directly incorporated into the regression model, while the distribution of some factors belonged to the long-tail distribution. We therefore take the natural logarithm for this part of the variable to ensure the data are more normally distributed [ 71 ]. Afterward, OLS, GWR, and MGWR models were constructed and evaluated for random distribution of residuals.…”
Section: Results and Analysismentioning
confidence: 99%
“…Around the characteristics and influencing factors of physical fitness mentioned in the introduction, a series of indicators are listed that may have an impact on the situation of low physical fitness of Chinese youth ( Table 1 and Table 2 ). As a composite concept, physical fitness has a wide range of influencing factors and needs to take into account regional indicators that are representative of each province in China, so the indicators for this study were selected from previous studies and existing established evaluation systems [ 63 , 70 , 71 ]. The indicators of regional characteristics such as the environment as well as socio-economic development selected for this study are based on attribute data from the China Statistical Yearbook 2018, China Environment Statistical Yearbook 2018, China Education Statistical Yearbook 2018, China Social Statistical Yearbook 2018, China’s 7th Population Census Bulletin, China’s provincial altitude barometric tables, and provincial statistical yearbooks for the year 2018.…”
Section: Methodsmentioning
confidence: 99%
“…Urban running trails can be broadly classified into three main types based on their location: streets, parks, and playgrounds. Many researchers have studied the association between physical activity and the environment of streets and parks (Chen et al, 2021; Su et al, 2014; Ying et al, 2015). It has been noticed that city dwellers do not only rely on parks, streets also allow a significant amount of physical activity (Lu, 2019; Lu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that the duration of physical activity on greenways is related to the distance between settlements, with proximity leading to a significant increase in activity (Humpel et al, 2004; Owen et al, 2004; Zhang et al, 2013). And a high degree function mixture or land-use mix can also encourage physical activity (Chen et al, 2021; Su et al, 2014; Ying et al, 2015). According to the study, trail continuity is a key factor affecting road runners' exercise experience (Majumdar et al, 2021).…”
Section: Introductionmentioning
confidence: 99%